Therapeutic waters as geotourism values of the Polish Baltic sea coast - Krawiec, Arkadiusz (Geotourism/Geoturystyka, 2018)
The oldest spa towns in the Polish Lowland have developed on the basis of brines from which salt used to be refined. This article presents conditions for the occurrence of medicinal (therapeutic) waters on the Polish Baltic Sea coast. It discusses the development of naturopathy in the area and presents brine water intakes and their utilisation. Moreover, the main tourist attractions of the spa towns and chances for the development of health tourism in the area are enumerated.